Peran Perempuan Dalam Pengelolaan Desa Wisata Tenganan Dauh Tukad, Kabupaten Karangasem, Bali - Alviawati, Vira Auli; Nugroho, Saptono; Ariwangsa, I Made Bayu (JURNAL DESTINASI PARIWISATA; Vol 12 No 1 (2024): VOL 12, NO 1 (2024): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2024.v12.i01.p02, 2024)
Tenganan Dauh Tukad Village is one of the villages included in Bali Aga village in Bali. Tourism in Tenganan Dauh Tukad Village has the main attraction in its culture. They have some unique traditions that can be witnessed by tourists. In line with the development of tourism in Tenganan Dauh Tukad Tourism Village, there are many types of job sectors. So that the purpose of this study is to find out what are the roles of women in Tenganan Dauh Tukad Tourism Village, especially in tourism management. This study used a qualitative approach with interactive data analysis techniques from Miles and Huberman. The data were obtained through observation for three months, interviews with women in Tenganan Dauh Tukad Tourism Village, and literature studies. This study used primary data and secondary data. The informant determination technique used is purposive sampling technique. The results of this study are alternatives and variations in the role of women in the implementation of Tenganan Dauh Tukad Tourism Village. The role of women is divided into 2 (two), namely the domestic role as housewives and the public role as workers. So that 3 (three) alternative roles are housewives, Female Worker, also housewives and Female worker at the same time (dwipera). The role of women in Tenganan Dauh Tukad Village is as a dual because some of them also work. With this dual role, women still participate in the management of Tenganan Dauh Tukad Tourism Village. But the role of men still dominates because the patriarchal system is still inherent in the life of the social and cultural reality of Balinese society. Keywords: Women's Role, Tourism Village, Tenganan Dauh Tukad, Management